2019
DOI: 10.1016/j.pbb.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous progesterone for cannabis withdrawal in women: Feasibility trial of a novel multimodal methodology

Abstract: Background: Sex differences in cannabis use disorder (CUD) and its treatment have been identified. Women report more severe withdrawal and have shown worse treatment outcomes. Ovarian hormones are implicated in these differences and research suggests that exogenous progesterone may be an effective pharmacotherapy. Methods: The current randomized, placebo-controlled, feasibility trial tested a novel multimodal methodology for administering exogenous progesterone during acute cannabis withdrawal. Eight heavy can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Moreover, exogenous progesterone was suggested as a therapy in women who suffer acute cannabis withdrawal symptoms due to its noticed effect in reducing cannabis craving. Large size and longer duration studies are needed to support the role of exogenous progesterone in the assessment of cannabis withdrawal symptoms [ 247 ]. The effects of other drugs on reducing cannabis withdrawal symptoms were also investigated, such as nabiximols, nefazodone, lofexidine, and oral THC; the results show their ability in the reduction in anxiety, sleep disorders, craving, and depressed mood, but they were associated with negative side effects that worsen withdrawal symptoms, such as irritability [ 248 , 249 ].…”
Section: Cannabis Poisoningmentioning
confidence: 99%
“…Moreover, exogenous progesterone was suggested as a therapy in women who suffer acute cannabis withdrawal symptoms due to its noticed effect in reducing cannabis craving. Large size and longer duration studies are needed to support the role of exogenous progesterone in the assessment of cannabis withdrawal symptoms [ 247 ]. The effects of other drugs on reducing cannabis withdrawal symptoms were also investigated, such as nabiximols, nefazodone, lofexidine, and oral THC; the results show their ability in the reduction in anxiety, sleep disorders, craving, and depressed mood, but they were associated with negative side effects that worsen withdrawal symptoms, such as irritability [ 248 , 249 ].…”
Section: Cannabis Poisoningmentioning
confidence: 99%
“…Synchronous or asynchronous video observation of medication-taking is a recent advance in clinical trials and well suited for inclusion in remote trials. Medication-taking can be observed via video connection with a staff member in real time (ie, synchronously 58 , 59 ), recorded via video on a mobile device and uploaded for subsequent staff review (ie, asynchronously 32 , 60 , 61 ), or automatically detected using a mobile app with facial recognition software, such as AICure. 62 Limitations of these methods include high participant burden, required access to technology with video capabilities, and the need for staff to observe dosing in real time or review videos at a later date (for synchronous and asynchronous methods, respectively).…”
Section: Remote Medication Adherence Monitoringmentioning
confidence: 99%
“…This may be attributed in part to the lower baseline cortisol found in the high ALLO group, but it is unclear to what extent this would account for the observed effect ( Milivojevic et al, 2016 ). In women that use cannabis, a small study found that progesterone could attenuate cannabis craving during a brief abstinence period ( Sherman et al, 2019 ). Further research is necessary to determine the reliability of this finding and if this effect extends to men.…”
Section: Neuroactive Steroidal Targetsmentioning
confidence: 99%